2018
DOI: 10.1038/s41422-018-0104-9
|View full text |Cite
|
Sign up to set email alerts
|

Plant HP1 protein ADCP1 links multivalent H3K9 methylation readout to heterochromatin formation

Abstract: Heterochromatin Protein 1 (HP1) recognizes histone H3 lysine 9 methylation (H3K9me) through its conserved chromodomain and maintains heterochromatin from fission yeast to mammals. However, in Arabidopsis, Like Heterochromatin Protein 1 (LHP1) recognizes and colocalizes genome-wide with H3K27me3, and is the functional homolog of Polycomb protein. This raises the question whether genuine HP1 homologs exist in plants. Here, we report on the discovery of ADCP1, a plant-specific triple tandem Agenet protein, as a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
89
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 50 publications
5
89
0
Order By: Relevance
“…inactive, GC-rich heterochromatin (9) inactive, AT-rich heterochromatin (8) active, intragenic (7) inactive, intragenic (6) inactive, Polycomb-regulated (5) inactive, intergenic (4) active, intragenic (3) inactive, intergenic (2) active, promoter/TSS ( . The H3K9me2 signal is the log-transformed average of two replicates normalized to H3, log 2 (H3K9me2/H3), as in [27]. Figure S9 Context-specific MET-JSD phaseplanes for CMT2-and RdDM-targeted TEs.…”
Section: ' 3'mentioning
confidence: 99%
See 2 more Smart Citations
“…inactive, GC-rich heterochromatin (9) inactive, AT-rich heterochromatin (8) active, intragenic (7) inactive, intragenic (6) inactive, Polycomb-regulated (5) inactive, intergenic (4) active, intragenic (3) inactive, intergenic (2) active, promoter/TSS ( . The H3K9me2 signal is the log-transformed average of two replicates normalized to H3, log 2 (H3K9me2/H3), as in [27]. Figure S9 Context-specific MET-JSD phaseplanes for CMT2-and RdDM-targeted TEs.…”
Section: ' 3'mentioning
confidence: 99%
“…c Hierarchical clustering of JSD (rosette) with histone marks. The H3K9me2 signal is log 2 (H3K9me2/H3) as in[27]. d Mean JSD in regions characterized by positive (x-axis) and negative (y-axis) HiC-eigenvalues (e).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, two groups have independently identified a functional plant HP1 homolog. Using a 3D-carbene SPRi platform to screen Arabidopsis ''Royal Family'' proteins that contain the Chromo, Tudor, PWWP, MBT, or Agenet domains, Shuai Zhao and colleagues from Tsinghua University, China, identified an Agenet domain-containing protein (ADCP1) showing strong binding activity preferentially with H3K9me2 peptide (Zhao et al, 2019). Meanwhile, Cuijun Zhang and colleagues from Shanghai Center for Plant Stress Biology, Chinese Academy of Sciences identified AGDP1, identical to ADCP1, by incubating nuclear extracts of Arabidopsis flowers with synthesized biotinylated H3K9me peptides followed by mass spectrometry analysis (Zhang et al, 2018).…”
mentioning
confidence: 99%
“…ADCP1/AGDP1 contains six conserved Agenet domains arranged as three tandem cassettes. Both Zhang et al (2018) and Zhao et al (2019) solved the structures of tandem Agenet domains in complex with an H3K9me2 peptide. Structure analyses revealed that the H3K9me2 peptide adopts a unique a helix and is well accommodated by an aromatic cage formed by two agent domains.…”
mentioning
confidence: 99%